2022
DOI: 10.1002/oby.23417
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐associated differences between BMI and SARS‐CoV‐2 antibody titers following the BNT162b2 vaccine

Abstract: Objective: This study investigated the sex-associated difference in the impact of obesity on antibody response to a COVID-19 vaccine.Methods: This study included 2,435 health care workers who received two doses of the BioNTech, Pfizer (BNT162b2) vaccine and participated in a serological survey, during which they were tested for anti-SARS-CoV-2 spike immunoglobin G (IgG) antibodies and asked for information on height, weight, and vaccination history via a questionnaire. Multivariable linear regression analysis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 16 publications
4
37
0
Order By: Relevance
“…Our findings in people with severe obesity are consistent with previous studies showing that the acute immune response to SARS-CoV-2 vaccines is comparable in people with obesity and normal weight people [15][16][17][18][19][20] . Some of these studies suggested that the duration of vaccineinduced immunity may be reduced in people with obesity [16][17][18] . These studies all relied on measurements of immunity at a single time-point and used different assays/endpoints (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings in people with severe obesity are consistent with previous studies showing that the acute immune response to SARS-CoV-2 vaccines is comparable in people with obesity and normal weight people [15][16][17][18][19][20] . Some of these studies suggested that the duration of vaccineinduced immunity may be reduced in people with obesity [16][17][18] . These studies all relied on measurements of immunity at a single time-point and used different assays/endpoints (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…People with obesity have impaired immune responses to conventional influenza, rabies and hepatitis vaccines [11][12][13][14] , however, the impact of obesity on their responses to mRNA and adenoviral vectored vaccines is not known. Some studies have suggested that following SARS-CoV-2 vaccination, antibody titres may be lower in people with obesity [15][16][17][18][19][20] . One possible explanation is the impact of needle length on vaccine dosing in people with obesity 21 .…”
Section: Mainmentioning
confidence: 99%
“…Current evidence regarding vaccine antibodies and the body mass index (BMI) is conflicting and scanty, perhaps partly because of differences in the distribution and physiology of fatty tissue in men compared to women. Yamamoto et al observed that a higher BMI was associated with lower titers of spike IgG antibodies against SARS-CoV-2 in men but not women ( 9 ). We found that BW positively correlated with antibody levels but not sex.…”
mentioning
confidence: 99%
“…Immunization with SARS-CoV-2 vaccines can be a global strategy to minimize deaths, severity, and overall disease burden of the pandemic [2]. While most recommended SARS-CoV-2 vaccines, such as BioNTech (BNT162b2) and Moderna (mRNA-1273) can achieve high efficacy [3], their immunogenicity can be hampered by several factors, e.g., aging, virus mutation [4,5], smoking [5], obesity [6,7], diabetes [7], and other underlying comorbidities [5]. Identification of such factors may be of public health significance regarding the prevention of the virus infection, e.g., administration of an earlier vaccine booster in high-risk groups [8].…”
Section: Introductionmentioning
confidence: 99%